The 12th Edition of the Scientific Days of the National Institute for Infectious Diseases "Prof. Dr. Matei Bals" and the 12th National Infectious Diseases Conference. Issue 3 (November 2016) - Niculae, Cristian-Mihail; Manea, Eliza; Jipa, Raluca; Merisor, Simona; Moroti, Ruxandra; Benea, Serban; Hristea, Adriana; Neguț, Alina; Săndulescu, Oana; Streinu-Cercel, Anca; Mărculescu, Dana; Andrei, Magdalena; et al.
Table of contents A1 The outcome of patients with recurrent versus non-recurrent pneumococcal meningitis in a tertiary health-care hospital in Bucharest Cristian-Mihail Niculae, Eliza Manea, Raluca Jipa, Simona Merisor, Ruxandra Moroti, Serban Benea, Adriana Hristea A2 Influence of bacteriophages on sessile Gram-positive and Gram-negative bacteria Alina Cristina Neguț, Oana Săndulescu, Anca Streinu-Cercel, Dana Mărculescu, Magdalena Lorena Andrei, Veronica Ilie, Marcela Popa, Coralia Bleotu, Carmen Chifiriuc, Mircea Ioan Popa, Adrian Streinu-Cercel A3 The utility of inflammatory biomarkers in the prognostic evaluation of septic patients – past, present and future Alina Orfanu, Cristina Popescu, Anca Leuștean, Remulus Catană, Anca Negru, Alexandra Badea, Radu Orfanu, Cătălin Tilișcan, Victoria Aramă, Ştefan Sorin Aramă A4 Etiologic and clinical features of bacterial meningitis in infants Constanța-Angelica Vișan, Anca-Cristina Drăgănescu, Anuța Bilașco, Camelia Kouris, Mădălina Merișescu, Magdalena Vasile, Diana-Maria Slavu, Sabina Vintilă, Endis Osman, Alina Oprea, Sabina Sandu, Monica Luminos A5 The diagnostic and prognostic role of neutrophil to lymphocyte count ratio in sepsis Alina Orfanu, Victoria Aramă, Ştefan Sorin Aramă, Anca Leuştean, Remulus Catană, Anca Negru, Gabriel Adrian Popescu, Cristina Popescu A6 Whooping cough in a HIV positive patient Ramona Georgiana Stanculete, Ana Vaduva Enoiu, Adelina Raluca Marinescu, Voichita Lazureanu A7Cronobacter sakazakii sepsis in varicella patient Adelina-Raluca Marinescu, Alexandru Crișan, Voichița Lăzureanu, Virgil Musta, Narcisa Nicolescu, Ruxandra Laza A8 Anaerobes an underdiagnosed cause of prosthesis joint infection Anca-Ruxandra Negru, Daniela-Ioana Munteanu, Raluca Mihăilescu, Remulus Catană, Olga Dorobăț, Alexandru Rafila, Emilia Căpraru, Marius Niculescu, Rodica Marinescu, Olivera Lupescu, Vlad Predescu, Adrian Streinu-Cercel, Victoria Aramă, Daniela Tălăpan A9Streptococcus pneumoniae meningitis presenting with normal CSF – case presentation Ramona Ștefania Popescu, Luminița Bradu, Dragoș Florea, Adrian Streinu-Cercel A10 Extrapulmonary manifestations of infection withMycoplasma pneumoniae – study on 24 cases Daniela Anicuta Leca, Elena Bunea, Andra Teodor, Egidia Miftode A11 The molecular diagnosis of severe bacterial sepsis in pediatric population Mădălina Merișescu, Gheorghiță Jugulete, Adrian Streinu-Cercel, Dragoș Florea, Monica Luminos A12 AcuteStaphylococcus aureus endocarditis with multiple septic complications in a patient with diabetes mellitus – case presentation Ramona Ștefania Popescu, Anamaria Dobrotă, Adina Ilie, Liliana Lucia Preoțescu A13 IsStreptococcus suis meningitis an under-diagnosed zoonosis? Adriana Hristea, Raluca Jipa, Nicoleta Irimescu, Irina Panait, Eliza Manea, Simona Merisor, Cristian Niculae, Daniela Tălăpan A14Klebsiella pneumoniae isolated from blood. Antimicrobial resistance – past and present Liana Cătălina Gavriliu, Otilia Elisabeta Benea, Șerban Benea, Alexandru Rafila, Olga Dorobăț, Mona Popoiu A15 Antibiotics resistance inStaphylococcus aureus isolated from blood cultures Livia Dragonu, Augustin Cupşa, Iulian Diaconescu, Irina Niculescu, Lucian Giubelan, Florentina Dumitrescu, Andreea Cristina Stoian, Camelia Guţă, Simona Puiu A16 Predominance of CTX-M enzymes in extended-spectrum β-lactamase-producing Enterobacteriaceae in two hospitals of Quebec City Bunescu Irina, Marilyse Vallée, Ann Huletsky, Dominique K. Boudreau, Ève Bérubé, Richard Giroux, Jean Longtin, Yves Longtin, Michel G. Bergeron A17 Postoperative meningoencephalitis withAcinetobacter baumannii XDR – a therapeutic challenge - Case report Cleo Nicoleta Roșculeț, Dalila-Ana Toma, Catrinel Ciuca, Daniela Tălăpan, Cătălin Apostolescu, Andrei Rogoz, Andrei Stangaciu, Viorica Mitescu, Tudor Vladoiu, Doina Iovănescu A18 Septic arthritis withBurkholderia cepacia Michaela Oana, Simona Costin A19 A novel approach for managing hard-to-treat infections Alina Cristina Neguț, Oana Săndulescu, Anca Streinu-Cercel, Maria Magdalena Moțoi, Mircea Ioan Popa, Adrian Streinu-Cercel A20 Nineteen months surveillance for multidrug resistant organisms (MDRO) by detecting asymptomatic colonization Daniela Tălăpan, Olga Mihaela Dorobăț, Mona Popoiu, Alexandru Mihai, Doina Iovănescu, Cleo Roşculeț, Cătălin Apostolescu, Gabriel-Adrian Popescu, Adrian Abagiu, Ruxandra Moroti-Constantinescu, Adriana Hristea, Victoria Aramă, Otilia Benea, Mădălina Simoiu, Rodica Bacruban, Adrian Streinu-Cercel, Alexandru Rafila A21 Antimicrobial resistance of Gram-positive cocci isolated from clinical specimens in the National Institute of Infectious Diseases "Prof Dr. Matei Balș" between 2009–2015 Olga Mihaela Dorobăț, Daniela Tălăpan, Alexandru Mihai, Ioana Bădicuț, Mona Popoiu, Alina Borcan, Alexandru Rafila A22 The high percentage of carbapenem-resistant Gram-negative bacilli in Romania: an analysis and some proposals Gabriel Adrian Popescu A23 Etiological, clinical and therapeutic considerations on 78 cases of healthcare associated meningitis or ventriculitis admitted in the "Sf. Parascheva" infectious diseases clinical hospital, Iași, from 2011 to 2015 Mihnea Hurmuzache, Georgiana Enache, Alexandra Ciocan, Mircea Bararu, Madalina Popazu A24 Nosocomial infection dynamics in an Intensive Care Department – an overview (epidemiological and clinical monitoring, advanced therapeutic intervention). Doina Viorica Iovănescu, Cleo Nicoleta Roșculeț, Andrei Rogoz Cătălin Gabriel Apostolescu, Viorica Mitescu, Tudor Vladoiu, Dalila Toma, Catrinel Ciuca A25 Safety and efficacy of interferon free treatment in patients with HCV chronic hepatitis- experience of a single Internal Medicine center Laura Iliescu, Georgiana Minzala, Letitia Toma, Mihaela Baciu, Alina Tanase, Carmen Orban A26 Viusid in treatment of chronic viral hepatitis B and C Victor Pantea, Gheorghe Placinta, Valentin Cebotarescu, Lilia Cojuhari, Paulina Jimbei A27 The management of hyperbilirubinemia in HCV cirrhotic patients who underwent therapy with direct acting antivirals Cristina Popescu, Anca Leuștean, Cristina Dragomirescu, Alina Orfanu, Cristina Murariu, Laurențiu Stratan, Alexandra Badea, Cătălin Tilișcan, Daniela Munteanu, Raluca Năstase, Violeta Molagic, Mihaela Rădulescu, Remulus Catana, Victoria Aramă A28 The efficacy of ombitasvir-paritaprevir/ritonavir, dasabuvir and ribavirin in patients with genotype 1 HCV compensated cirrhosis Cristina Popescu, Laurențiu Stratan, Remulus Catana, Anca Leuștean, Cristina Dragomirescu, Alexandra Badea, Cristina Murariu, Raluca Năstase, Violeta Molagic, Daniela Munteanu, Cătălin Tilișcan, Mihaela Rădulescu, Alina Orfanu, Ioan Diaconu, Anca Negru, Iulia Bodosca, Violeta Niță, Victoria Aramă A29 The efficacy of direct acting antivirals regimen without ribavirin in HCV genotype 1b infected patients with compensated cirrhosis Anca Leuștean, Victoria Aramă, Alina Orfanu, Remulus Catana, Laurențiu Stratan, Cristina Dragomirescu, Cristina Murariu, Alexandra Badea, Cătălin Tilișcan, Daniela Munteanu, Violeta Molagic, Raluca Năstase, Mihaela Rădulescu, Cristina Popescu A30 Liver decompensation during ombitasvir-paritaprevir/ritonavir-dasabuvir and ribavirin regimen in HCV infected patients with Child-Pugh A cirrhosis Cristina Popescu, Cristina Dragomirescu, Anca Leuștean, Cristina Murariu, Laurențiu Stratan, Alexandra Badea, Remulus Catană, Alina Orfanu, Raluca Mihaela Năstase, Violeta Molagic, Daniela Munteanu, Cătălin Tilișcan, Victoria Aramă A31 The safety of direct acting antivirals in HCV compensated cirrhotic patients - an interim analysis Victoria Aramă, Remulus Catană, Cristina Dragomirescu, Cristina Murariu, Anca Leuștean, Laurențiu Stratan, Alexandra Badea, Alina Orfanu, Anca Negru, Raluca Năstase, Violeta Molagic, Daniela Munteanu, Cătălin Tilișcan, Mihaela Rădulescu, Ioan Diaconu, Violeta Niță, Iulia Bodoșca, Cristina Popescu A32 The access of patients with HCV compensated cirrhosis to the National Program of therapy with direct acting antivirals Cristina Popescu, Alexandra Badea, Anca Leuștean, Alina Orfanu, Anca Negru, Laurențiu Stratan, Cristina Dragomirescu, Remulus Catană, Cristina Murariu, Violeta Molagic, Raluca Năstase, Cătălin Tilișcan, Daniela Munteanu, Mihaela Rădulescu, Ioan Diaconu, Violeta Niță, Iulia Bodoșca, Victoria Aramă A33 Severe reactivation of chronic hepatitis B after discontinuation of nucleos(t)ide analogues – a case series Cristina Popescu, Alina Orfanu, Anca Leuștean, Alexandra Badea, Laurențiu Stratan, Remulus Catană, Cătălin Tilișcan, Victoria Aramă A34 The dynamic of hematological disorders during direct acting antivirals therapy for HCV compensated cirrhosis Cristina Popescu, Cristina Murariu, Cristina Dragomirescu, Anca Leuștean, Laurențiu Stratan, Alina Orfanu, Alexandra Badea, Remulus Catană, Anca Negru, Cătălin Tilișcan, Daniela Munteanu, Mihaela Rădulescu, Violeta Molagic, Raluca Mihaela Năstase, Ioan Alexandru Diaconu, Iulia Bodoșca, Violeta Niță, Victoria Aramă A35 Behaviors, attitudes and risk factors for viral hepatitis in international medical students vs. the general population in Romania Yagmur Erturk, Oana Săndulescu, Alina Cristina Neguț, Claudiu Mihai Șchiopu, Adrian Streinu-Cercel, Anca Streinu-Cercel A36 Characteristics of hepatitis C virus reactivation due to immunosuppressive therapy in Romanian HCV infected patients with hematological malignancies Violeta Molagic, Cătălin Tilișcan, Cristina Popescu, Raluca Mihăilescu, Daniela Munteanu, Raluca Năstase, Anca Negru, Angelica Tenita, Victoria Aramă, Ștefan Sorin Aramă A37 The dynamic IFN-gamma serum levels during successful peginterferon-a 2a/ribavirin therapy in HCV chronic infection Simona Alexandra Iacob, Diana Gabriela Iacob, Monica Luminos A38 Overlapping risk factors for transmission of HBV, HCV and HIV in the general population in Romania Anca Streinu-Cercel, Oana Săndulescu, Mioara Predescu, Alexandra Mărdărescu, Cătălin Tilișcan, Mihai Săndulescu, Claudiu Mihai Șchiopu, Adrian Streinu-Cercel A39 Acute hepatitis - an uncommon neurological complication Cleo Nicoleta Roșculeț, Catrinel Olimpia Ciuca, Dalila Ana Toma, Cătălin Gabriel Apostolescu, Andrei Rogoz, Cristina Elena Mitu, Andrei Stangaciu, Viorica Daniela Mitescu, Tudor Gheorghe Vladoiu, Doina Viorica Iovănescu A40 Regression of liver fibrosis following sustained virological response in patients with chronic HCV infection and cirrhosis Oana Săndulescu, Anca Streinu-Cercel, Monica Andreea Stoica, Liliana Lucia Preoțescu, Daniela Manolache, Gabriela Jana Ceapraga, Maria Magdalena Moțoi, Luminița Bradu, Adina Ilie, Gabriela Mircea, Ionel Durbală, Adrian Streinu-Cercel A41 Preliminary results of treatment with sofosbuvir and daclatasvir of patients with chronic hepatitis C Irina Russu, Tiberiu Holban, Tatiana Pantilimonov, Galina Chiriacov, Arcadie Macvovei, Elena Scorohodico, Oleg Dmitriev A42 HIV-syphilis coinfection Diana Alexandra Costache, Anca Benea, Eliza Manea, Cristian Niculae, Raluca Jipa, Adriana Hristea, Elisabeta Benea, Ruxandra Moroti, Șerban Benea A43 Thrombophilia – additional risk factor for the evolution of pregnancy in HIV-positive patients Mihai Mitran, Carmen Georgescu, Loredana Mitran, Simona Vladareanu A44 The incidence of oropharyngeal candidiasis in hospitalized HIV infected pediatric Romanian cohort between 1 January - 31 December 2015 Andreea Ioana Magirescu, Viorica Andreev, Cristina Nicolau, Alexandra Largu, Carmen Dorobat, Carmen Manciuc A45 TB incidence in HIV infected patients during the year of 2015 Viorica Andreev, Andreea Ioana Magirescu, Ina Isac, Cristina Nicolau, Alexandra Largu, Carmen Dorobat, Carmen Manciuc A46 Retrospective analysis of HIV/AIDS deaths recorded in the Clinical Infectious Diseases Hospital, Constanța in the period 01 January 2014–30 June 2016. Epidemiological considerations. Iulia Gabriela Șerban, Ghiulendan Resul, Consuela Marcaș A47 Acute liver failure with favorable evolution in an HIV-HBV coinfected patient Iosif Marincu, Patricia Poptelecan, Bogdan Trincă, Sorina Mitrescu, Anca Tudor, Daliborca Vlad, Livius Tirnea A48 Lifestyle impact on HIV management Nurcan Baydaroglu, Alina Cristina Neguț, Oana Săndulescu, Daniela Manolache, Gabriela Ceapraga, Monica Andreea Stoica, Anca Streinu-Cercel, Adrian Streinu-Cercel 49. HIV positive mothers newborns - clinical experience from January 2012 to June 2016 Carmen Manciuc, Mariana Pagute, Cristina Nicolau, Carmen Dorobăț, Alexandra Largu A50 Rediscovering HIV-associated progressive multifocal leukoencephalopathy and HIV encephalopathy: clinical suspicion and subsequent brain autopsies Ioan-Alexandru Diaconu, Laurențiu Stratan, Daniela Ion, Luciana Nichita, Cristina Popescu, Raluca Năstase, Daniela Munteanu, Violeta Molagic, Cătălin Tilișcan, Mihaela Rădulescu, Alexandra Diaconu, Anca Negru, Alina Orfanu, Cristina Dragomirescu, Remulus Catană, Anca Leuștean, Irina Duport-Dodot, Cristina Murariu, Iulia Bodoșca, Violeta Niță, Alexandra Badea, Victoria Aramă A51 Antenatal surveillance of pregnant women with risk behavior and its impact on mother-to-child HIV transmission in Romania Mariana Mărdărescu, Cristina Petre, Marieta Iancu, Rodica Ungurianu, Alina Cibea, Ruxandra Drăghicenoiu, Ana Maria Tudor, Delia Vlad, Sorin Petrea, Carina Matei, Dan Oțelea, Carmen Crăciun, Cristian Anghelina, Alexandra Mărdărescu A52 Noninvasive assessments (APRI, Fib-4, transient elastography) of fibrosis in patients with HIV and HIV/HBV infection Elena Dumea, Adrian Streinu-Cercel, Sorin Rugină, Lucian Cristian Petcu, Stela Halichidis, Simona Claudia Cambrea A53 Undetectable HIV viral load – the main goal in the management of HIV-infected patients Carmen Chiriac, Nina-Ioana Bodnar, Iringo-Erzsebet Zaharia-Kezdi, Cristina Gîrbovan, Andrea Incze, Anca Meda Georgescu A54 LPS serum levels and correlation with immunological, virological and clinical outcome in HIV infected patients Simona Alexandra Iacob, Diana Gabriela Iacob, Eugenia Panaitescu, Monica Luminos, Manole Cojocaru A55 LL37 human cathelicidin serum levels are positively correlated with IFN gamma and alanine aminotransferase level in HCV infection Simona Alexandra Iacob, Diana Gabriela Iacob, Monica Luminos A56 Early diagnosis of pulmonary tuberculosis in a non-compliant HIV/AIDS late presenter patient Vochita Laurențiu, Vochita Andreia, Opreanu Radu, Trinca Bogdan, Rosca Ovidiu, Marincu Iosif A57 Evolution of antiretroviral regimens in naϊve patients in 2016 Ramona Zamfir, Alina Angelescu, Alena Andreea Popa, Raluca Jipa, Ruxandra Moroti, Adriana Hristea, Liana Gavriliu, Șerban Benea, Elisabeta Benea A58 The unfavorable risk factors for HIV infected persons with positive blood cultures hospitalized at the National Institute for Infectious Diseases "Prof. Dr. Matei Balș" in 2015 Alena-Andreea Popa, Georgeta Ducu, Daniela Camburu, Alina Cozma, Manuela Podani, Roxana Dumitriu, Liana Gavriliu, Șerban Benea, Elisabeta Benea A59 Epidemiological aspects of HIV infection in Oltenia region Andreea Cristina Stoian, Florentina Dumitrescu, Augustin Cupșa, Lucian Giubelan, Irina Niculescu, Loredana Ionescu, Livia Dragonu A60 HIV risk behaviors and prevalence among patients in methadone maintenance therapy (MMT) from Arena center, Bucharest Adrian Octavian Abagiu, Loredana Nicoleta Stoica, Catrinel Blaga, Archontis Koulosousas, Roxana Ștefănescu, Alice Atomoaie, Florentina Paraschiv, Florin Matache Duna A61 Therapeutic options in a case of severe psoriasis associated with both HIV infection and hepatitis C virus previously treated with fumaric acid esters Rodica Olteanu, Roxana Ion, Alexandra Zota, Isra Ennour Jaballah, Lara Mahfoud, Georgeta Preda, Magda Constantin A62 Prevalence of autoantibodies against gangliosides in asymptomatic HIV-infected patients Ilinca Nicolae, Corina Daniela Ene, Mădălina Irina Mitran, Vasile Benea, Mircea Tampa, Simona Roxana Georgescu A63 Subclinical inflammation in HIV-infected patients undergoing antiretroviral therapy – a cross sectional study Iulia Cristina Bodoșca, Cristina Murariu, Cătălin Tilișcan, Victoria Aramă, Cristina Popescu, Daniela Munteanu, Mihaela Rădulescu, Violeta Molagic, Raluca Năstase, Alina Orfanu, Anca Leuștean, Remulus Catană, Anca Negru, Adrian Streinu-Cercel, Sorin Aramă A64 Severe Guillain-Barré syndrome occurring after chickenpox with favorable evolution Iuliana CAramăngiu, Ovidiu Rosca, Monica Cialma, Radu Opreanu, Laurențiu Vochita, Iosif Marincu A65 Echovirus 30 infection with pulmonary and cardiac complications – case report Vlad Murărescu, Marilena Palaghiță, Alina Cristina Neguț, Cornel Camburu, Adrian Streinu-Cercel A66 Herpetic encephalitis with favorable evolution in an adult immunocompetent patient Irina Duşan, Patricia Poptelecan, Bogdan Trincă, Sorina Mitrescu, Livius Tirnea, Iosif Marincu A67 Clinical-evolutional aspects in present-day measles Narcisa Nicolescu, Alexandru Crișan, Voichița Lăzureanu, Ruxandra Laza, Virgil Musta, Adelina-Raluca Marinescu, Andreea Bîrlad A68 Pneumococcal superinfection in children with influenza Victor Daniel Miron, Anca Cristina Drăgănescu, Constanța-Angelica Vișan, Anuța Bilașco, Daniela Pițigoi, Oana Săndulescu, Monica Luminița Luminos A69 Varicella complicated with transverse myelitis - case presentation Monica Luminos, Endis Osman, Magdalena Vasile, Anca Cristina Drăgănescu, Constanța-Angelica Vișan, Anuța Bilașco, Camelia Kouris, Sabina Șchiopu, Mădălina Merișescu A70 Clinical forms of enterovirus infections during the summer season of 2016 Monica Luminos, Anca Cristina Drăgănescu, Constanța-Angelica Vișan, Anuța Bilașco, Camelia Kouris, Endis Osman, Sabina Vintilă, Magda Vasile, Mădălina Merișescu A71 Face off – HIV and lymphoma – case series presentation Liana Cătălina Gavriliu, Otilia Elisabeta Benea, Alina Angelescu, Ramona Zamfir, Daniela Camburu, Georgeta Ducu, Alina Cozma, Roxana Dumitriu, Manuela Podani, Șerban Benea, Mihaela Ionică A72 Coxsackie infection complicated by pancytopenia – pediatric case report Gheorghiță Jugulete, Adina Stăncescu, Cristina Elena Popescu, Luminița Marin, Diana Zaharia, Cristina Dumitrescu, Lucia Tudor, Sabina Vintilă A73 Viral respiratory infections in children in the season 2015–2016 Constanța-Angelica Vișan, Anca Cristina Drăgănescu, Anuța Bilașco, Magda Vasile, Mădălina Merișescu, Camelia Kouris, Cristina Negulescu, Endis Osman, Diana-Maria Slavu, Sabina Vintilă, Daniela Pițigoi, Monica Luminos A75 The severity of A H1N1 Influenza infection in the 2015–2016 season Cleo Roșculeț, Catrinel Olimpia Ciuca, Dalila Toma, Cătălin Apostolescu, Andrei Rogoz, Andrei Stangaciu, Viorica Mitescu, Doina Iovănescu, Cornel Camburu, Bogdana Manu A76 Acute respiratory distress syndrome in a child with measles Ana Vaduva-Enoiu, Ramona Georgiana Stanculete, Adelina Raluca Marinescu, Voichita Elena Lazureanu A77 Management challenges of right-sided infectious endocarditis in an HIV positive patient – case presentation Elena-Violeta Niță, Sînziana Dumitru, Daniela-Ioana Munteanu, Anca Ruxandra Negru, Remulus Catană, Ioan Diaconu, Bogdana Manu, Ligia Ionescu, Liliana Ion, Cătălin Tilișcan, Victoria Aramă A78 Bacterial infection in critical patients with severe A H1N1 influenza virus infection (epidemiology, development, therapeutic decisions) Doina Viorica Iovănescu, Cleo Nicoleta Roșculeț, Andrei Rogoz, Cătălin Apostolescu, Viorica Mitescu, Tudor Vladoiu, Dalila Toma, Catrinel Ciuca A79 Epidemiological aspects of severe acute respiratory infection cases (SARI) in the season 2015–2016, in the Clinical Hospital of Infectious Diseases – Constanța, Romania Iulia Gabriela Șerban, Marioara Neacșu A80Overexpression of IL-6 trans signaling pathway in viral infections Simona Roxana Georgescu, Vasile Benea, Corina Daniela Ene, Mircea Tampa, Cristina Iulia Mitran, Ilinca Nicolae A81 Acute viral hepatitis B with persistent HBsAg – description and evolution George Ciprian Pribac, Mirandolina Prisca, Fulvia Ursoiu, Carmen Neamtu, Bogdan Totolici, Coralia Cotoraci, Aurel Ardelean A82 Prevalence of cervical pathogens in a population of pregnant female patients monitored in a tertiary care hospital in Bucharest, Romania Simona Elena Albu, Mara Carsote, Beatrice Miclăuș, Diana Mihai, Oana Săndulescu, Cristina Vasiliu A83 Prevalence of group BStreptococcus during pregnancy in a cohort of patients monitored in a tertiary care hospital in Bucharest, Romania Cristina Vasiliu, Mara Carsote, Corina Gorgoi, Beatrice Miclăuș, Diana Mihai, Oana Săndulescu, Simona Elena Albu A84 Infectious hematoma in the gastrocnemius muscle – case presentation Amelia Blescun, Gelu Breaza A85 Reflections towards the underexplored HTLV Romanian viral circulation - adult T‐cell leukemia/lymphomas, a case series Sabina Vintila, Felicia Mihai, Meilin Omer, Cornel Dragan, Daniela Pitigoi A86 A febrile confusion syndrome with acute onset – case presentation Mirela Ciucu, Marius-Dan Ionescu, Cristina Roskanovic, Valentina Barbu, Iulian Diaconescu, Florentina Dumitrescu, Irina Niculescu A87 Retrobulbar optic neuritis in a HIV-positive patient - case report Mihaela Ionică, Ramona-Alexandra Zamfir, Alina Cozma, Otilia Elisabeta Benea A88 A rare presentation of Q fever – case presentation Alexandra-Sînziana Dumitru, Daniela-Ioana Munteanu, Violeta Niță, Cristina Popescu, Iulia Bodosca, Angelica Tenita, Viorica Ispas, Victoria Aramă A89 Tinea incognita – case presentation Vasile Benea, Simona Roxana Georgescu, Mircea Tampa, Diana Oana Leahu, Cristina Maria Safta, Mihaela Anca Benea A90 Incidence and risk factors associated with TORCH infections during pregnancy Oana Săndulescu, Octavian Munteanu, Roxana Bohâlțea, Livia Trașcă, Monica Cîrstoiu A91 Acute respiratory failure in critical patients with sepsis Doina Viorica Iovănescu, Cleo Nicoleta Roșculeț, Andrei Rogoz, Cătălin Gabriel Apostolescu, Viorica Daniela Mitescu, Tudor Gheorghe Vladoiu, Dalila Toma, Catrinel Ciuca A92 Cochleo-vestibular deficit secondary toGranulicatella elegans meningitis Mădălina Georgescu A93 Influenza 2015/2016 – clinical, epidemiological and virological characteristics of cases admitted in three infectious diseases hospitals Daniela Pițigoi, Alina Elena Ivanciuc, Mihaela Lazar, Teodora Ionescu, Carmen Maria Cherciu, Cristina Țecu, Maria Elena Mihai, Maria Nițescu, Rodica Bacruban, Delia Azamfire, Aura Dumitrescu, Elena Ianosik, Daniela Leca, Elena Duca, Andra Teodor, Codrina Bejan, Emanoil Ceaușu, Simin-Aysel Florescu, Corneliu Popescu, Grațiela Târdei, Codrina Juganariu, Emilia Lupulescu A94 Severe complications of varicella requiring hospitalization in previously healthy children in Brașov county Ligia Rodina, Maria Elena Cocuz A95 Clinical forms ofClostridium difficile colitis in children Gheorghiță Jugulete, Adina Stăncescu, Cristina Elena Popescu, Luminița Marin, Diana Zaharia, Cristina Dumitrescu, Endis Osman A96 Community-acquired pneumonia – demographic, clinical and etiological aspects Irina Niculescu, Augustin Cupșa, Iulian Diaconescu, Florentina Dumitrescu, Livia Dragonu, Andreea Stoian, Lucian Giubelan, Cristina Roskanovic A97 Acute myocarditis in an adult patient with chickenpox - Case report Ramona-Alexandra Zamfir, Mihaela Ionica, Otilia-Elisabeta Benea A98 Caustic oropharyngeal wound with acute group F streptococcal superinfection mimicking diphtheria – case report and differential diagnosis Maria-Cristina Sîrbu, AnaMaria Dobrotă, Alina Cristina Neguț, Roxana Duda, Rodica Bacruban, Daniela Pițigoi, Cristiana Cerasella Dragomirescu, Daniela Tălăpan, Olga Dorobăț, Adrian Streinu-Cercel, Anca Streinu-Cercel A99Clostridium difficile infection in HIV-positive patients admitted in the National Institute for Infectious Diseases "Prof. Dr. Matei Balș" in 2015 Mihaela Ionica, Ramona-Alexandra Zamfir, Alina Cozma, Otilia Elisabeta Benea A100 Title: Epidemiology ofCandida oral infections (stomatitis) in Romania Sergiu Fendrihan, Ecaterina Scortan, Mircea Ioan Popa A101 Anthrax case series in south-eastern Romania Corneliu P Popescu, Șerban N Benea, Andra E Petcu, Adriana Hristea, Adrian Abagiu, Iuliana A Podea, Raluca E Jipa, Georgeta Ducu, Raluca M Hrișcă, Dragoș Florea, Manuela Nica, Eliza Manea, Simona Merișor, Cristian M Nicolae, Simin A Florescu, Irina M Dumitru, Emanoil Ceaușu, Sorin Rugină, Ruxandra V Moroti A102 Knowledge, risk perception and attitudes of healthcare workers at the National Institute for Infectious Diseases "Prof. Dr. Matei Balș" regarding Ebola Daniela Pițigoi, Teodora Ionescu, Oana Săndulescu, Maria Nițescu, Bogdan Nițescu, Iulia Monica Mustaţă, Sorina Claudia Boldeanu, Florentina Furtunescu, Adrian Streinu-Cercel A103 A case of abdominopelvic actinomycosis with successful short-term antibiotic treatment Diana Gabriela Iacob, Simona Alexandra Iacob, Mihaela Gheorghe A104 A case of pneumonia caused byRaoultella planticola Iulian Diaconescu, Irina Niculescu, Floretina Dumitrescu, Lucian Giubelan A105 Vitamin D deficiency and sepsis in childhood Adriana Slavcovici, Raluca Tripon, Roxana Iubu, Cristian Marcu, Mihaela Sabou, Monica Muntean A106 The clinical and epidemiological aspects and prophylaxis of Lyme disease among patients who presented with tick bites to the Clinical Infectious Disease Hospital "Toma Ciorbă" Ion Chiriac, Tiberiu Holban, Liviu Tazlavanu A107 Drug-resistant tuberculosis in HIV infected patients Raluca Jipa, Eliza Manea, Roxana Cernat, Kezdi Iringo, Andrei Vâță, Manuela Arbune, Teodora Moisil, Adriana Hristea A108 Kidney injury molecule-1 and urinary tract infections Corina-Daniela Ene, Ilinca Nicolae, Roxana Simona Georgescu A109 The impact of microbiological agents on serum gangliosides in patients with benign prostate hyperplasia Corina-Daniela Ene, Cosmin-Victor Ene, Roxana Simona Georgescu, Marilena Ciortea, Lucreția Dulgheru, Ilinca Nicolae A110 Toxocariasis - the experience of the Iași Infectious Diseases Hospital between 2013–2015 Mihaela Cătălina Luca, Ioana-Alina Harja-Alexa, Roxana Nemescu, Mădălina Popazu, Andrei Ștefan Luca A111 Species of anaerobic Gram-positive cocci involved in odontogenic abscesses Gabriela Bancescu, Bogdan Dabu, Adrian Bancescu A112Clostridium difficile infection recurrences Eliza Manea, Raluca Jipa, Adriana Hristea A113 Differential diagnosis of staphylococcal and tuberculous osteodiscitis – case report Adina Elena Ilie, Săftica-Mariana Pohrib, Alina Cristina Neguț, Maria-Sabina Tache, Maria Magdalena Moțoi, Oana Săndulescu, Ion Aurel Iliescu, Adrian Streinu-Cercel A114 Severe clinical forms of respiratory syncytial virus infections Cristina Tecu, Maria-Elena Mihai, Mihaela Lazăr, Carmen Cherciu, Alina Ivanciuc, Daniela Pițigoi, Emilia Lupulescu A115Acinetobacter baumannii postoperative sepsis associated withClostridium difficile enterocolitis in an immune suppressed elderly patient Mirela Paliu, Manuela Curescu, Bianca Cerbu, Iosif Marincu A116 Risk factors and their impact on psychopathology and quality of life among people living with HIV/AIDS in Romania Fulvia Ursoiu, Mirandolina Prișcă, George Ciprian Pribac A117 Antivirals susceptibility of influenza viruses circulating in Romania Maria Elena Mihai, Carmen Maria Cherciu, Alina Elena Ivanciuc, Cristina Tecu, Emilia Lupulescu A118 Retrospective study of hospitalized cases of sepsis at the Hospital Clinic of Infectious Diseases "Toma Ciorbă" Irina Bunescu, Tiberiu Holban, Ana Pasnin, Stela Semeniuc, Raisa Popovici, Galina Chiriacov